SAT0260 MUSCULAR INVOLVEMENT OF THE LOWER LIMBS IN PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHIES: A MRI EVALUATION. (June 2019) - Barsotti, Simone; Mugellini, Barbara; Tripoli, Alessandra; Aringhieri, Giacomo; Cardelli, Chiara; Cioffi, Elisa; Zampa, Virna; Caramella, Davide; Mosca, Marta; Neri, Rossella
Abstract : Background: Since many years, muscular magnetic resonance imaging (MRI) has been used in the diagnosis and follow-up of patients with idiopathic inflammatory myopathies (IIM), but the clinical significance and the pattern of the muscular alterations (edema, fatty infiltration and atrophy) in different subsets of the disease are still not well defined. Objectives: The aims of this study were to analyse possible differences in the involved muscles between dermatomyositis (DM) and polymyositis (PM); the correlations between the pattern of muscular involvement in different subsets of the disease and disease parameters in a monocentric cohort of patients. Methods: We retrospectively collected data from 85 patients with poly and dermatomyositis (EULAR/ACR criteria) who performed pelvic and tights muscle MRI from January 2010 to December 2018: 27 had DM and 58 PM, mean age 58.6±13.4 years, mean disease duration of 45±73 months. The images in 22 muscles for the presence of muscular edema, fatty infiltrates and atrophy were assessed by a dedicated radiologist. Moreover, data about serum creatine kinase (CK) and manual muscle test 8 (MMT8) were collected. Data were reported as median±interquartile range; non-parametric tests were used for the analysis. Results: Sixty-three patients presented muscular edema in at least one muscle. Patients with muscular edema had higher CK levels (1506±1976 vs 235±224 p<0.001) lower disease duration (9.5±47.0 vs 19.8±97.2 p=0.031). and lower MMT8 (63.6±11.2 vs 69.8±10.7 p=0.031). Forty-eight patients presented fatty infiltrates that were more frequent in older patients (63.1±11-3 vs 52.8±13.7 p=0.01) and in those with longer disease duration (39.1±95.4 vs 9.5±12.5 p=0.024). CK levels and MMT8 were not different in patients with or without muscular fatty infiltrates. With the multivariate analysis the disease duration represents the only independent factor for the presence of muscular fatty infiltrates (p=0.05). Muscular atrophy was present in 17 patients but it was not correlated to age and disease duration. CK and MMT8 were not different in presence/absence of fatty infiltrates or muscular atrophy. Edema and atrophy were not different between poly- and dermatomyositis. The fatty infiltrate was more present in the posterior compartment of the tights (biceps femoris and semitendinosus muscle) in patients with PM compared to DM (68.2% vs 29.6% p=0.046). Conclusion: The alterations identified with MRI in our cohort changed according to the disease duration and the age of the patients. In particular, fatty infiltration was more frequent in patients with longer disease duration, but was not associated to CK levels and muscular weakness. Moreover, fatty infiltration was prevalent in the posterior compartment of the tights in PM patients. Muscular MRI is widely used in the diagnosis and follow-up but the clinical meanings of the different alterations still need to be investigated. Disclosure of Interests: Simone Barsotti: None declared, Barbara Mugellini: None declared, Alessandra Tripoli: None declared, Giacomo Aringhieri: None declared, Chiara Cardelli: None declared, Elisa Cioffi: None declared, Virna Zampa: None declared, Davide Caramella: None declared, Marta Mosca Paid instructor for: GlaxoSmithKline, Lilly, UCB, Rossella Neri: None declared